Evaluation of bankruptcy yields as a method of forecasting the financial and economic state of an enterprise - О.V. Shavurska (Економіка, управління та адміністрування)
Bankruptcy forecasting becomes a priority, which will identify the main problems and shortcomings at the enterprise, as well as take into account the impact of various external factors, and as a result to predict the probability of bankruptcy and take measures to avoid it. The economic essence of the concept of «bankruptcy» is considered and the own definition of this concept is proposed, which takes into account its economic, social and legal meaning. The causes of the crisis at the enterprise are described. In the crisis of domestic enterprises, it is important to be able to anticipate the first manifestations of financial insolvency, which in the future may lead to bankruptcy, so the diagnosis and prevention of negative factors is important. The main tasks of the analysis of bankruptcy diagnostics are determined. Foreign and domestic methods of analysis of the probability of bankruptcy of the enterprise are characterized, their advantages, disadvantages and possibility of application are defined. The stages of the economic analysis of diagnostics of a crisis condition and threat of bankruptcy of the enterprise are proposed. Based on the analysis of the advantages and disadvantages of bankruptcy probability methods, the integrated indicator of bankruptcy probability is proposed, which will allow to determine the possibility of the threat of bankruptcy probability for domestic enterprises. The integrated indicator of the probability of bankruptcy, which takes into account all the main indicators of the financial and property condition of the enterprise, and its calculation will allow to identify the threat of bankruptcy.